The importance of MDP priming, silica blasting or glazing on the retention force of Y-TZP copings to varying geometry tooth abutments - Ramos, Nathália C. [UNESP]; Alves, Larissa M. M. [UNESP]; Ramos, Gabriela F. [UNESP]; Bottino, Marco Antonio [UNESP]; Melo, Renata M. [UNESP]; Souza, Rodrigo Othávio A. (MDPI, 2021)
To evaluate the influence of the convergence angle of tooth preparations and abutments height and several surface treatments for zirconia copings through the tensile retention test. 120 crown preparations were made in Nema G10 with the maxillary first molar anatomy. In total, 60 abutments of 5 mm height were divided into two groups of 6◦ and 20◦ convergence angles of tooth preparations, and 60 abutments with a convergence angle of tooth preparations of 12◦ were divided into groups of 4 and 6 mm heights. Three surface treatments used were MDP-primer (10-Methacryloyloxydecyl dihydrogen phosphate), glazing or silica blasting. The abutments were scanned to make zirconia copings (3Y-TZP–Yttria-Stabilized Tetragonal Zirconia Polycrystals, Vita In-Ceram YZ). After cementation, the mechanical cycling (2 × 106 cycles, 3 Hz, 100 N) was performed to aging. After cycling, the copings were tested in tensile (1 kN load cell; 0.5 mm/s speed). Both abutments support base and copings were embedded in acrylic resin with the aid of a device that maintained the long axis perpendicular to the horizontal plane. Data were analyzed with the two-way ANOVA and Tukey test (95%). ANOVA revealed that the convergence angle influenced the tensile retention (p = 0.0232), but the abutments height showed no statistically significant difference (p = 0.086). The MDP-primer and silica blasting showed higher retention forces in the specimens with height variations. For bonded zirconia crowns, the retention force provided by high convergence angle preparation is critical and cannot be improved by surface treatments. For short and long crown preparations, MDP-based Primers or Silica blasting are advisable to aid restoration longevity.
Keywords: Dental bonding; Dental prosthesis failures; Tensile strength; Tooth preparation; Y-TZP ceramic